2021
DOI: 10.1093/g3journal/jkab230
|View full text |Cite
|
Sign up to set email alerts
|

Selective functional inhibition of a tumor-derived p53 mutant by cytosolic chaperones identified using split-YFP in budding yeast

Abstract: Life requires the oligomerization of individual proteins into higher-order assemblies. In order to form functional oligomers, monomers must adopt appropriate three-dimensional structures. Molecular chaperones transiently bind nascent or misfolded proteins to promote proper folding. Single missense mutations frequently cause disease by perturbing folding despite chaperone engagement. A misfolded mutant capable of oligomerizing with wild-type proteins can dominantly poison oligomer function. We previously found … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Yeast cells were stained for viability using Evans Blue and mitochondrial ROS using dihydrorhodamine (Gomez et al 2014). All microscopy work was done using EVOSfl all-in-one Olympus microscope (Advanced Microscopy Group, Bothell, WA) as described (Denney et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Yeast cells were stained for viability using Evans Blue and mitochondrial ROS using dihydrorhodamine (Gomez et al 2014). All microscopy work was done using EVOSfl all-in-one Olympus microscope (Advanced Microscopy Group, Bothell, WA) as described (Denney et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We saw no PM mislocalization or dominant-negative functional effects in previous studies with these same BiFC-tagged versions of Cdc3 and Cdc10 (Denney et al, 2021;Garcia et al, 2016;Weems & McMurray, 2017), but in those studies, the tagged septins were expressed at endogenous levels from the native promoters. We systematically manipulated individual features of the BiFC co- First, we made an improved version of the plasmid.…”
Section: Aberrant Plasma Membrane Localization Of Bifc Signalmentioning
confidence: 78%
“…However, previous studies have shown that even a single divergent amino acid between Ssa1 and Ssa2 can produce differences in their ability to modulate prion propagation and protein degradation [ 36 ]. A recent study observed a parallel defect in septin levels in Ssa1-expressing yeast [ 37 ]. Future research, possibly involving a comparative interactome study of Ssa proteins, may shed light on this issue [ 34 ].…”
Section: Discussionmentioning
confidence: 99%